The obsidian chamber - Preston, Douglas J.; Child, Lincoln (New York : Grand Central Publishing, a division of Hachette Book Group, 2016)
After a harrowing, otherworldly confrontation on the shores of Exmouth, Massachusetts, Special Agent A.X.L. Pendergast is missing, presumed dead. Sick with grief, his ward, Constance, retreats to her chambers beneath the family mansion at 891 Riverside Drive -- only to be taken captive by a shadowy figure from the past.
Keywords: Pendergast, Aloysius (Fictitious character) -- Fiction; Government investigators -- Fiction; Suspense fiction; Detective and mystery fiction